Novel Approaches to Monitor Pharmacokinetics and Metabolism of Gemcitabine-Ibandronate Conjugate in Mice and Dogs - Jost Klawitter; Mckay Easton; Alexander Karpeisky; Kristen B. Farrell; Douglas H. Thamm; Touraj Shokati; Uwe Christians; Shawn Patrick Zinnen (Molecules)
Background. The use of the bone-seeking properties of bisphosphonates (BPs) to target the delivery of therapeutic drugs is a promising approach for the treatment of bone metastases. Currently, the most advanced example of this approach is a gemcitabine-ibandronate conjugate (GEM-IB), where the bone-targeting BP ibandronate (IB) is covalently linked to the antineoplastic agent gemcitabine (GEM) via a spacer phosphate group. In the present study, we describe the development of a new analytical platform to evaluate the metabolism and pharmacokinetics of GEM-IB in mice and dogs and the results of proof-of-concept studies assessing the pharmacokinetics of GEM-IB in dogs and mice. Methods. We validated analytical platforms to analyze GEM-IB and five of its major metabolites IB, gemcitabine-5′-phosphate (GEMMP), gemcitabine (GEM), 2′,2′-difluoro-2′-deoxyuridine-5′-phosphate (dFdUMP), and 2′,2′-difluoro-2′-deoxyuridine (dFdU) and performed proof-of-concept pharmacokinetic studies in mice (5 mg/kg i.p.) and dogs (5 mg/kg i.v.). Results. Intra- and inter-run accuracy and imprecision (3 days) of the assays met the (FDA) acceptance criteria. The proof-of-concept plasma pharmacokinetic studies in mice showed AUCs of 1278, 10,652, 405, 38, 1063, 3389, and 38 h·ng/mL for GEM-IB, IB, GEMMP, dFdU-MP, GEM, and dFdU, respectively. In dog plasma, AUCs of 295, 5725, 83, 11, 1625, and 6569 h·ng/mL were observed for GEM-IB, IB, GEMMP, dFdUMP, GEM, and dFdU. Conclusions. Pharmacokinetic studies in dogs and mice showed that GEM-IB is rapidly converted to IB and GEM; dFdU is formed (from GEM) with a delay. The rapid disappearance of GEM-IB from circulation could be explained by a combination of metabolism and rapid distribution to tissue/bone.